Incidence of steroid modified tinea in pediatric age group at tertiary centre in North India - Chaudhary, Savita; Jain, Chandni; Paliwal, Gaurav; Shukla, Priyanka (International Journal of Research in Dermatology, 2021)
Background: Uncontrolled use and abuse of topical steroids has led to increase in number of cases of superficial dermatophytosis of skin, hair and nail in pediatric age group as well. Our study aimed to analyse epidemiological and microbiological profile of steroid modified tinea (SMT) in pediatric age group. Methods: Clinically diagnosed tinea childhood patients with history of usage of topical steroids in children were included in our study. Detailed history was taken and clinical examination along with KOH mount and culture was done. Results: 112 patients were clinically diagnosed as tinea out of which 61cases gave the history of topical steroids and were included in our study. Most common age group was 12-18 years with female:male of ratio approximately 3:1 and disseminated and atypical form was the most common variety. KOH mount was positive in 73.2% cases and culture was positive in 69.6% cases. Most common species found out to be Tinea mentagrophytes followed by Tinea rubrum. Among non-dermatophyte group, Candida was the commonest. Conclusions: There is rise in incidence of dermatophytosis, especially steroid modified, atypical and disseminated.